Management implications following the reconstruction of the small and shallow Lake Mustijärv (Estonia) - Tammeorg, Olga; Kiani, Mina; Nõges, Peeter; Blank, Kätlin; Feldmann, Tõnu; Haberman, Juta; Laugaste, Reet; Seller, Siim; Tuvikene, Arvo; Tammeorg, Priit (Page Press Publications, 2024)
Lake Mustijärv was reconstructed by sediment removal following an almost complete siltation. Here we evaluate challenges and opportunities for the management of the lake. We focused on the stream discharging to the lake (i.e., external loading), sediment retention in accumulation basins (i.e., internal processes) as well as the ecosystem-level response to stressors based on biological variables (phyto- and zooplankton, macrophytes, fishes and zoobenthos). Urban and agricultural inputs elevated ammonium and total phosphorus concentrations in the lake, challenging lake reconstruction efforts. Sediment transport highly increased the risk of faster filling of the lake, associated with upstream streambed excavation. Sediments trapped at the accumulation basins release nutrients that enhance eutrophication. We, however, observed a rapid recovery in fish, macrophytes, and zoobenthos, despite the significant disturbances. Lake Mustijärv is in eutrophic condition, reflected by phytoplankton (Pseudanabaena, Closteriopsis dominance) and zooplankton (Keratella, Polyarthra dominance) composition. To improve lake water quality will require controlling external nutrient inputs, underlining the importance of better coordinated activities between the local (lake restoration) and regional (catchment use) scales.
Keywords: ecosystem dynamics; nutrient loading; nutrient retention; longitudinal catchment study; sediment removal